2018
DOI: 10.3389/fpsyg.2018.00278
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Grammars and Their Diverging Evolutionary and Processing Paths: Evidence From Functional MRI Study of Serbian

Abstract: We address the puzzle of “unity in diversity” in human languages by advocating the (minimal) common denominator for the diverse expressions of transitivity across human languages, consistent with the view that early in language evolution there was a modest beginning for syntax and that this beginning provided the foundation for the further elaboration of syntactic complexity. This study reports the results of a functional MRI experiment investigating differential patterns of brain activation during processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…The reason for the difficulty of using the insights about the nature of syntactic representations and computation to inform our knowledge about functional organization of the brain and vice versa was said to lie in the inherent mismatch in conceptual granularity as well as ontological incompatibility between the concrete biological units of neuroscience and the abstract syntactic postulates (Poeppel and Embick, 2005). We propose that the considerations of the evolution of syntax, as outlined in Progovac (2015, 2016), provide a way of bringing together the postulates from Theoretical Syntax and Cognitive Neuroscience (see also Progovac et al, 2018). This framework, by contrasting modern structures (syntax) with ancestral structures (proto-syntax), introduces linguistic constructs of the granularity commensurate with the tools used in neuroscience to probe the neural correlates of syntactic computation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for the difficulty of using the insights about the nature of syntactic representations and computation to inform our knowledge about functional organization of the brain and vice versa was said to lie in the inherent mismatch in conceptual granularity as well as ontological incompatibility between the concrete biological units of neuroscience and the abstract syntactic postulates (Poeppel and Embick, 2005). We propose that the considerations of the evolution of syntax, as outlined in Progovac (2015, 2016), provide a way of bringing together the postulates from Theoretical Syntax and Cognitive Neuroscience (see also Progovac et al, 2018). This framework, by contrasting modern structures (syntax) with ancestral structures (proto-syntax), introduces linguistic constructs of the granularity commensurate with the tools used in neuroscience to probe the neural correlates of syntactic computation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it may be possible to isolate certain brain networks that are specialized for processing structures of different degrees of syntactic elaboration, as reflected in the stages of language evolution. The rationale behind this proposal is that complex, uniquely human, grammatical patterns require more support by the most recently evolved/enhanced neural networks than do their flatter proto-syntactic counterparts, which in turn may show a less streamlined and more diffuse distribution across the brain, as well as more individual variability (Progovac et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the processing of Serbian middles, relative to (phonologically and semantically) matched transitive accusative counterparts, would result in reduced activation in the Broca's-basal ganglia network (Progovac et al 2018a). We found that the processing of transitives, compared to middles, indeed showed an increase in activation in the basal ganglia bilaterally.…”
Section: Fossil Middles Split-accusativity and The Processing Of Thmentioning
confidence: 82%
“…Especially noteworthy is the contrast between absolutive-like middles (a,b examples below), which exhibit animacy effects, and the (default) accusative grammars, illustrated in the (c) Consistent with this analysis, absolutive-like se structures seem to be processed differently by the brain, in comparison to transitive accusative struc-tures. Progovac et al (2018a) report the results of an fMRI experiment which was designed to test the processing of vP-less se middles in Serbian, in comparison to their semantically matched accusative counterparts with vP. We specifically looked at the differential role played by the Broca's-basal ganglia network in processing ancestral versus more modern types of structures because several recent findings suggest that this network has been bolstered relatively recently in evolution, through selection, by increased synaptic plasticity and neuronal connectivity (e.g.…”
Section: Fossil Middles Split-accusativity and The Processing Of Thmentioning
confidence: 99%